Building Industry 4.0 Awareness through the Implementation of Internet of Things-Based Wastewater Measurement in Yogyakarta’s Hotel Industry - Qodri, Muhammad Fatih; Pratama, Bagus Gilang; Verdiansyah, Okki; Permana, Irvan Ardhi; Lawinu, Nodyka Elkawi (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
The advancement of Industry 4.0 has brought the integration of digital technologies, such as the Internet of Things (IoT), into various industries, including hotel industry. However, awareness of Industry 4.0 technologies in hotel operations remains limited, particularly in sustainable practices. This paper aims to build awareness of Industry 4.0 by implementing IoT-based wastewater measurement systems in the hotel industry in Yogyakarta City. The community engagement involves the design and deployment of an IoT-based system to monitor wastewater quality, providing real-time data to hotel operators. The methods include system integration and pilot testing in selected hotel in Yogyakarta in collaboration with Indonesian Hotel and Restaurant Association (PHRI). Results show that the implementation of IoT technology can enhance monitoring accuracy and support the sustainability efforts of hotels by reducing water pollution. The conclusions show the potential of IoT in driving environmental sustainability in the hospitality industry, while also demonstrating the practical application of Industry 4.0 technologies in day-to-day hotel operations. This initiative bridges the gap between modern technological adoption and sustainable practices in the hotel industry.